의료기관 종사자의 심폐소생술 교육에 관한 연구 - 이현숙(Hyun-Suk Lee); 임청환(Cheong-Hwan Lim); 박해리(Hae-Ri Park); 정홍량(Hong-Ryang Jung); 양오남(Oh-Nam Yang) (방사선기술과학, 2018)
Most schools and educational institutions, as well as most companies, show willingness to teach CPR. However, as an essential element for the health care workers, this study aims to analyze the appropriate timing of education and improvements to the education, focusing on those who have trained for CPR. The survey was conducted for only those who applied for CPR education regardless of their profession in medical institutions. There were 105 males and 93 females by gender, and an average of 198 females were 33.5 years. The difference in CPR education depending on individual characteristics showed a high demand that all research subjects' gender, age and marital status should be improved to a practical education. During the education period, the efficiency of CPR was high. It is expected that the education of CPR will be used for the improvement of the training cycle and the training content since it is the enhancement of the performance capabilities that require practical application.